Navigating Stormy, Uncharted Waters - Camdessus, Michel (International Monetary Fund, 1998)
This paper explains various challenges posed by the new global economy for the IMF. The urgent tasks of restoring stability to crisis-ridden countries have been accompanied by other more far-reaching questions. The five speeches included in this collection cover a broad range of activities and thinking over the past year. The themes range from immediate crisis management to the broad questions of a new architecture for the global economy; and from the specific concerns of individual countries and regions to the conditions for a strong and equitable world economy. One of the speeches, delivered in September 1998, steps back from prevailing worldwide market turbulence, seeking lessons from the crises, and stressing that conditions vary extensively among emerging economies. Clear, calm analysis is essential by market participants to differentiate among economies. Another speech sets out initial thoughts not just on the key elements of a new financial architecture, however, also on the role that can be played by each constituency in the world economy.